56 Evaluating the choosing wisely questions: a pilot study of methods to engage consumers in health decisions across health literacy levels. (4th December 2019) - Muscat, Danielle; Chang, Edward; Thompson, Rachel; Tracy, Marguerite; Cvejic, Erin; Zadro, Joshua; Smith, Jessica; Lindner, Robyn; McCaffery, Kirsten
Abstract : Background: There are widespread efforts to involve consumers in shared decision making about tests and treatments that may be unnecessary or even harmful. However, it is increasingly clear that consumers need support and confidence to be involved in health decisions with their healthcare providers, and this may be particularly important for patients with lower health literacy. One initiative that has gained momentum worldwide is Choosing Wisely. As part of this international campaign, five questions have been developed to support conversations between patients and providers about unnecessary tests, medications and procedures. However, the questions have not been evaluated in terms of their impact or their acceptability, and their use among people with different levels of health literacy is unknown. Researchers have also suggested that interventions to support shared decision making should include two stages – 'preparation' followed by 'enablement' – to be more successful. However, this two-tiered approach remains untested in regards to the Choosing Wisely five questions. Aim: To pilot test the relative effectiveness of preparation and enablement interventions among people with different health literacy levels to inform the design and sample size for a larger trial. Method: Design, setting, participants: Randomised controlled trial in Australian adults aged >18 years, recruited via an online market research company. Intervention: We developed a video for the preparation intervention and selected the Choosing Wisely Australia® 5 questions as the enablement intervention. Randomisation : 164 participants were presented with a hypothetical lower back pain scenario and randomised to one of three intervention groups (preparation alone [n=55]; enablement alone [n=58]; both [n=51]), stratified by health literacy. Primary outcomes: Mean difference (from baseline to follow-up) in self-efficacy to ask questions and be involved in health decisions, and intention to engage in shared decisions about low-value care. Results: The preparation video alone resulted in a significantly greater increase in self-efficacy to be involved in health decisions compared to the enablement questions alone (6.93 vs 3.80; p =0.044). An intervention-by-health literacy interaction was observed for intention to engage in shared decisions ( p =0.025). For those with higher health literacy, the combined intervention yielded the greatest change in intention, followed by the preparation video, whereas the enablement questions resulted in no meaningful change. However, for individuals with lower health literacy, the enablement questions alone demonstrated the greatest change in intention followed by combined intervention, with the preparation video alone resulting in little-to-no change. Conclusion: In this pilot study, preparation and enablement interventions had a differential impact across health levels on supporting involvement in health decisions. We will discuss these findings and present preliminary data from our larger randomised controlled trial evaluating the effectiveness of these interventions in a sample of 1020.